Carcass characteristics of the marketed Matabele goat from south-western Zimbabwe - Simela, L.; Ndlovu, L.R.; Sibanda, Lindiwe Majele (Elsevier, 1999)
Weight, dimensions, composition and yield indices of half-carcasses of 52 male (milk-teethed to full mouth) and 18 mature female (6-8 teeth) goats were examined to provide information on the characteristics of Matebele goat carcasses of different ages and sexes in order to identify those that may be used in an objective appraisal of local goat carcasses. Side length, chest depth, thigh circumference and eye muscle area (EMA) increased significantly (P0.05) with age. There were no significant differences (P>0.05) in carcass dimensions between sexes of mature goats, except EMA, which was greater (P0.05). The major difference between carcasses of mature male and female goats was due to the heavier bone and forequarters (P